Uji Pemberian Dosis Pupuk Daun terhadap Pertumbuhan dan Hasil Tanaman Tebu (Saccharum officinarum L.) Terbakar - Anang Dwi Febrianto; Setyo Budi; Wiharyanti Nur Lailiyah (JINTAN : Jurnal Ilmiah Pertanian Nasional, 2022)
Sugar production has decreased due to the fertilization method. One solution is to apply the proper dose of fertilization. The purpose of this study was to determine the application of various doses of foliar fertilizer on the growth and yield of the JR 01 variety at the age of 7 months burned in Gresik Regency. This study used a Randomized Block Design with one factor, namely P0 (control), P1 (cow urine fertilizer 20 ml/liter), P2 (cow urine fertilizer 40 ml/liter), P3 (cow urine fertilizer 60 ml/liter), P4 (Petrovita fertilizer 3 ml/liter), P5 (Petrovita fertilizer 6 ml/liter), and P6 (Petrovita fertilizer 9 ml/liter). Each was repeated four times so that there were 28 experimental units with observation variables, including growth variables (increase in stem height, stem diameter, number of stems, number of segments, number of tillers) and yield variables (Brix, yield, weight per cane stalk (g plant-1) and weight per cane stalk (t ha-1). Observational data were then analyzed using analysis of variance (ANOVA). If there was a significant difference, proceed with the Least Significant Difference test (LSD) 5% and correlation test. In the growth variable, the highest significant differences were between ages 44, 46, and 48 weeks after planting (WAP) and the use of cow urine fertilizer on the variable number of tillers. While in the yield variable, there was the highest significant difference at the age of 44 WAP using petrovita fertilizer on the Brix and yield variables. There was a significant correlation with a very strong and unidirectional relationship between the growth and yield variables. Effective treatment in increasing growth in the number of tillers, namely P2 (cow urine fertilizer 40 ml/liter), effective therapy in increasing Brix yield, and the yield is P5 (Petrovita fertilizer 6 ml/liter).